2016
DOI: 10.1038/gt.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, high-level hepatic secretion of acid α-glucosidase for Pompe disease achieved in non-human primates using helper-dependent adenovirus

Abstract: Pompe disease (glycogen storage disease type II (GSD-II)) is a myopathy caused by a genetic deficiency of acid α-glucosidase (GAA) leading to lysosomal glycogen accumulation causing muscle weakness, respiratory insufficiency and death. We previously demonstrated in GSD-II mice that a single injection of a helper-dependent adenovirus (HD-Ad) expressing GAA resulted in at least 300 days of liver secretion of GAA, correction of the glycogen storage in cardiac and skeletal muscles and improved muscle strength. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Within 72 h of intravenous vector administration, NK cells in the spleen acquired a highly activated state manifested by the expression of perforin, granzyme B, and IFN-c and the expression of these cytotoxic effectors in NK cells was completely dependent on functional IFN-I signaling. Intravenous delivery of HAdv-based vectors devoid of all viral genes, so-called 'gutless' vectors [93,94], results in a greatly prolong transgene expression in the liver of mice [95,96], dogs [97,98], and nonhuman primates [22,99,100]. The same group demonstrated that the principal NK cell-activating receptor NKG2D is required for the NK cell-mediated cytolysis of virus-infected cells [92].…”
Section: Functional Consequences Of Innate Immune Activation By Hadv mentioning
confidence: 99%
See 1 more Smart Citation
“…Within 72 h of intravenous vector administration, NK cells in the spleen acquired a highly activated state manifested by the expression of perforin, granzyme B, and IFN-c and the expression of these cytotoxic effectors in NK cells was completely dependent on functional IFN-I signaling. Intravenous delivery of HAdv-based vectors devoid of all viral genes, so-called 'gutless' vectors [93,94], results in a greatly prolong transgene expression in the liver of mice [95,96], dogs [97,98], and nonhuman primates [22,99,100]. The same group demonstrated that the principal NK cell-activating receptor NKG2D is required for the NK cell-mediated cytolysis of virus-infected cells [92].…”
Section: Functional Consequences Of Innate Immune Activation By Hadv mentioning
confidence: 99%
“…It is apparent that certain early viral genes encoded in the HAdv genome and expressed in hepatocytes after systemic delivery of replication-deficient first-generation vectors are direct activators of NK cell-mediated cytotoxicity. Intravenous delivery of HAdv-based vectors devoid of all viral genes, so-called 'gutless' vectors [93,94], results in a greatly prolong transgene expression in the liver of mice [95,96], dogs [97,98], and nonhuman primates [22,99,100]. Although NK cell-mediated toxicity is avoided by deleting all viral genes, systemic delivery of 'gutless' viruses still potently activates acute systemic inflammatory responses that are driven entirely by interaction of virus capsid with innate immune cell compartments.…”
Section: Functional Consequences Of Innate Immune Activation By Hadv mentioning
confidence: 99%
“…As HD-Ad do not contain any viral genes, this late toxicity is not observed, which allows a long-term transgene expression as observed in small (Kim et al 2001; Toietta et al 2005) and large animal models (Morral et al 1999; Brunetti-Pierri et al 2006). This has allowed successful long-term phenotypic correction of various liver monogenic disorders (Brunetti-Pierri and Ng 2011), among which haemophilia A (Reddy et al 2002; Hu et al 2011), haemophilia B (Ehrhardt and Kay 2002), OTC deficiency (Mian and Lee 2002), glycogen storage disease 1A (Koeberl et al 2007), Criggler-Najjar syndrome (Schmitt et al 2014), primary hyperoxaluria type 1 (Castello et al 2016), acute intermittent porphyria (Unzu et al 2013), phenylketonuria (Cerreto et al 2012), familial hypercholesterolaemia caused by mutations in the LDLR (Nomura et al 2004) and ApoE genes (Belalcazar et al 2003) in rodents, haemophilia A (Brown et al 2004; McCormack et al 2006) and B (Ehrhardt et al 2003; Brunetti-Pierri et al 2005), glycogen storage disease type 1 (Crane et al 2012) in dogs, and haemophilia A and B and Pompe disease (Rastall et al 2016) in non human primates.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
“…Reddy et al 2002;H ue ta l2011), haemophilia B(Ehrhardt and Kay 2002), OTC deficiency(Mian and Lee 2002), glycogen storage disease 1A(Koeberl et al 2007), Criggler-Najjar syndrome(Schmitt et al 2014), primary hyperoxaluria type 1(Castello et al 2016), acute intermittent porphyria(Unzu et al 2013), phenylketonuria(Cerreto et al 2012), familial hypercholesterolaemia caused by mutations in the LDLR(Nomura et al 2004) and ApoE genes(Belalcazar et al 2003) in rodents, haemophilia A(Brown et al 2004;McCormack et al 2006) and B(Ehrhardt et al 2003;Brunetti-Pierri et al 2005), glycogen storage disease type 1(Crane et al 2012) in dogs, and haemophilia A and B and Pompe disease(Rastall et al 2016) in non human primates.…”
mentioning
confidence: 99%
“…In addition, a recent gene therapy study in non-human primates showed that delivering helper-dependent adenovirus expressing GAA to the liver produced sufficient secreted GAA for uptake by multiple muscles 52 . One advantage of using splice switching PMOs to address Pompe patients with c.-32-13T > G mutation is that when delivered through intravenous injections, these compounds accumulate in the liver and kidney 49 .…”
Section: Discussionmentioning
confidence: 99%